An efficient technique for the numerical solution of the bidomain equations. - Whiteley, J (2008)
Computing the numerical solution of the bidomain equations is widely accepted to be a significant computational challenge. In this study we extend a previously published semi-implicit numerical scheme with good stability properties that has been used to solve the bidomain equations (Whiteley, J.P. IEEE Trans. Biomed. Eng. 53:2139-2147, 2006). A new, efficient numerical scheme is developed which utilizes the observation that the only component of the ionic current that must be calculated on a fine spatial mesh and updated frequently is the fast sodium current. Other components of the ionic current may be calculated on a coarser mesh and updated less frequently, and then interpolated onto the finer mesh. Use of this technique to calculate the transmembrane potential and extracellular potential induces very little error in the solution. For the simulations presented in this study an increase in computational efficiency of over two orders of magnitude over standard numerical techniques is obtained.